Difference In The Quality Of Storage Power And Randang Lokan Hedonic Test - Maysya, Rameza Nabilah; Elida, Elida; Gusnita, Wiwik; Zulfikar, Dikki (Universitas Negeri Padang, 2024)
This research is motivated by local food innovations that are processed using lokan basic ingredients from the South Coast and West Pasaman. The difference in the origin of the lokan area used will produce the resulting physical, chemical and sensory characteristics. This can affect a person's storage capacity and likability level. This study aims to analyze the shelf life and describe a person's preference for lokan randang by using the origin of different lokan areas. This type of research is a mixed method using qualitative methods for storage capacity and quantitative methods for hedonic tests of randang lokan. The data collection technique in this study is using observation and questionnaires. The data obtained using the t-test method, the results of the questionnaire were tabulated in the form of tables and level tests to find out the comparison of a person's level of preference for different randang lokan. The results show .